Pengaruh Kualitas Produk dan Harga Terhadap Loyalitas Pelanggan Pempek 299 di Lampung Tengah - Parlin Queen, Kelin; Toton, Toton (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
In the era of globalization like today, we must often hear and talk about the business world, a sector that is developing in Central Lampung, namely food, namely Pempek 299. This study was conducted with the aim of knowing the influence of product quality and price on customer loyalty in Pempek 299 partially and simultanously. The population in this research, namely Pempek 299 consumers in 2020 as many as 975 consumers based on data from Pempek 299 consumers. The research sample totaled 91 respondents. Collecting data by means of interviews, observations, documentation and questionnaires. The analysist technique is in the form of validity test, reliability test, multiple linear regressions analysist, determination coefficientR2, hypothesis testing. The research results show 1. Product Quality has a significant positive effect on Customer Loyalty at Pempek 299 in Central Lampung. 2 Price has a significant positive effect on Customer Loyalty at Pempek 299 in Central Lampung. 3. Product Quality and Price have a significant positive effect on Customer Loyalty at Pempek 299 in Central Lampung.